الشفاء بتعریف حقوقِ مصطفیٰ ﷺ کا تعارفی و تجزیاتی مطالعہ: An Analytical Study of the “Al-Shifā Ba Ta‘rīf-e-Ḥuqūq-e-Muṣṭafā” - Nawaz, Muhammad; Fazal Haq, Muhammad (Al-Amīr Research Journal for Islamic Studies, 2020)
The most prominent and living name among the African biographers is Qazi Ayaz Mālkī. His book “Al-Shifā Ba Ta‘rīf-e-Ḥuqūq-e-Muṣṭafā” has an important place in the books of Sīrah and also has the status of the most popular book among all kinds of people. This book is also called Kitab-e-Shifā (meaning the one who revives hearts and heals from heart diseases). The reason for writing this book was that the people were becoming oblivious to the obligatory status and virtues of the Holy Prophet ﷺ and were becoming completely incapable of paying their dues. In these circumstances, the demand for preparation and compilation of a collection of rights and manāqibs related to it became intense and he compiled this magnificent book. On the one hand, it teaches love and respect for the Prophet (peace and blessings of Allah be upon him) and on the other hand, it mentions his rights and rewards for fulfilling them. The writing style of the book is simple and smooth as well as eloquent. The book is not so long that it would be too long for the reader to comprehend, nor is it so short that it would not be possible to get access to the concepts and demands due to its brevity. The people have made this book their favorite and have been studying it and the biographers have adopted Al-Shifā as an authoritative and reliable source. Because of its importance and usefulness, an introductory and analytical study of this book will be presented in this article.